Forty‐eight cases of leiomyosarcoma of bone in Japan: A multicenter study from the Japanese musculoskeletal oncology group. Issue 4 (15th June 2016) - Mori, Tomoaki; Nakayama, Robert; Endo, Makoto; Hiraga, Hiroaki; Tomita, Masato; Fukase, Naomasa; Kobayashi, Eisuke; Kawai, Akira; Ueda, Takafumi; Morioka, Hideo
Abstract : Background: Leiomyosarcoma of bone (LMSoB) is a rare malignant bone tumor. This multicenter retrospective study was conducted to investigate the diagnosis and the clinical outcome of primary LMSoB in Japan. Methods: Forty‐eight patients (average age: 52 years [range 14–88 years]) with primary LMSoB who were treated at registered institutes in Japan between 1991 and 2014 were recruited. The median follow‐up period was 44 months (range: 2–273). Results: The 5‐year overall survival rates and disease‐free survival rates were 78.3% and 44.9%, respectively. Surgical treatment was performed in 42 patients, and R0 resection was achieved in 31 patients. Neoadjuvant chemotherapy was administered in 18 patients. The most common regimen (cisplatin‐based chemotherapy) was administered in 15 patients, however, no patient achieved a good response in both radiological and histological evaluations. The presence of metastasis at the first visit and a lack of definitive surgery were significantly correlated with poor overall survival, and the surgical margin was a significant prognostic factor for disease‐free survival. Conclusions: This study is the largest LMSoB case series ever reported. Surgical treatment with wide margins was the only treatment that proved to be effective, whereas adjuvant chemotherapy in the present setting did not improve the overall survival. J. Surg. Oncol. 2016;114:495–500 . © 2016 Wiley Periodicals, Inc.